Transcriptome Analysis of Resistant and Susceptible Sorghum Lines to the Sorghum Aphid (Melanaphis sacchari (Zehntner)) - Minghui Guan; Junli Du; Jieqin Li; Tonghan Wang; Lu Sun; Yongfei Wang; Degong Wu (Agriculture, 2025)
The sorghum aphid (Melanaphis sacchari (Zehntner, 1897)), a globally destructive pest, severely compromises sorghum yield and quality. This study compared aphid-resistant (HX133) and aphid-susceptible (HX37) sorghum (Sorghum bicolor (L.) Moench) cultivars, revealing that HX133 significantly suppressed aphid proliferation through repellent and antibiotic effects, while aphid populations increased continuously in HX37. Transcriptome analysis identified 2802 differentially expressed genes (DEGs, 45.9% upregulated) in HX133 at 24 h post-infestation, in contrast with only 732 DEGs (21% upregulated) in HX37. Pathway enrichment highlighted shikimate-mediated phenylpropanoid/flavonoid biosynthesis and glutathione metabolism as central to HX133’s defense response, alongside photosynthesis-related pathways common to both cultivars. qRT-PCR validation confirmed activation of the shikimate pathway in HX133, driving the synthesis of dhurrin—a cyanogenic glycoside critical for aphid resistance—and other tyrosine-derived metabolites (e.g., benzyl isoquinoline alkaloids, tocopherol). These findings demonstrate that HX133 employs multi-layered metabolic regulation, particularly dhurrin accumulation, to counteract aphid infestation, whereas susceptible cultivars exhibit limited defense induction. This work provides molecular targets for enhancing aphid resistance in sorghum breeding programs.